Does an Upper Endoscopy Before Transesophageal Echocardiography Change Patient Management?. Issue 10 (November 2015) - Zuchelli, Tobias; Alsheik, Eva; Chu, Christopher; Bhandari, Bhavik
Abstract : Goal: To determine if esophagogastroduodenoscopy (EGD) before transesophageal echocardiography (TEE) will change patient management. Background: Before TEE gastroenterologists are often consulted to evaluate patients with a history of dysphagia, known gastrointestinal (GI) disease, or GI bleed. There are no known published data on the clinical utility of EGD before TEE. Design and Setting: Retrospective study at an inner city tertiary-care center. Patients: A total of 134 patients were included who were at least 18 years old and underwent an EGD to evaluate the safety of the blind passage of a TEE probe. Results: In total, 134 patients were identified. Twenty patients (15%) were not cleared for TEE due to esophageal surface abnormalities (n=3; esophagitis, ulcer, mucosal tear), esophageal structural abnormalities (n=10; varices, stricture, ring, web, hernia, Zenker), and combinations thereof (n=7). Of the 20 patients not cleared for TEE, 17 never underwent a TEE and 3 patients underwent a TEE 7 to 180 days later. Two patients undergoing EGD and 5 patients undergoing TEE experienced adverse cardiopulmonary events. Conclusions: Our results demonstrate that an EGD before TEE can elucidate findings that may preclude the passage of a blind probe in patients with upper GI symptoms or known esophageal disease. Therefore, we propose that an EGD is clinically beneficial before TEE and can change patient management. Abstract : Supplemental Digital Content is available in the text.